How Oxygen Absorption Affects the Al2O3‐Encapsulated Blue Phosphorene–Au Alloy. Issue 8 (25th June 2021) - Faraone, Gabriele; Martella, Christian; Bonera, Emiliano; Molle, Alessandro; Grazianetti, Carlo
Abstract : The urgent quest to introduce the Xenes, a new family of graphene‐like materials, into everyday technological devices furthers demands for a specific understanding of their reactivity to different environments. Herein, the role of oxygen on blue phosphorene fragments alloyed with the Au(111) substrate, the so‐called BlueP–Au alloy, is investigated both on a microscopic scale and at the interface with Al2 O3, commonly used to protect Xenes in ambient conditions. Although molecular oxygen does not affect the BlueP–Au alloy or intercalate below it, the role of oxygen is fundamental to relieve the charging effects at the very interface between Al2 O3 and the BlueP–Au alloy when exposed to air. These findings highlight the importance of combining different tools, including microscopy and spectroscopy, to ascertain the stability of 2D materials in device‐ready configurations. Abstract : The role of oxygen absorption in blue phosphorene alloyed with a gold substrate, the so‐called BlueP–Au alloy, and on Al2 O3 ‐encapsulated BlueP–Au alloy, is investigated combining microscopic and spectroscopic characterization tools, thus showing that aging in environmental conditions relieves the charging effects at the very interface between the capping layer and the metal–phosphorus network.